Diversity and metabolomic characterization of Penicillium expansum isolated from apples grown in Argentina and Spain. Issue 9 (September 2022) - Maldonado, María Luisa; Patriarca, Andrea; Mc Cargo, Patricia; Iannone, Leopoldo; Sanchis, Vicente; Nielsen, Kristian Fog; Fernández Pinto, Virginia
Abstract: Apples ( Malus domestica ) are one of the most consumed fruits globally. It is a relevant crop in Argentina and Spain, and one of the main fruits for export and industrialization in these countries. Quality control of apples, fundamentally in the postharvest stage, is critical to prevent fungal diseases. The blue mould, caused by Penicillium expansum, is responsible for great economic losses due to the deterioration of the fruit and mycotoxin production. Many studies have characterized this pathogen; however, little is known about the differences between populations from distant geographical origins. The objective of the present study was to characterize two P. expansum populations, from Argentina and Spain, through morphological, metabolomic and molecular approaches, and to evaluate the existence of differences related to their geographical source. A total of 103 isolates, 53 from Argentina and 50 from Spain were studied. Their morphological features were consistent with the species description. The secondary metabolite profiles revealed low chemical diversity. All 103 isolates shared the production of 13 compounds, namely andrastins, aurantioclavine, chaetoglobosins, communesins, expansolides, roquefortine C and patulin. Penostatins and citrinin were produced by 102 and 101 isolates, respectively. A region of the β-tubulin gene was selected to analyse the diversity of the P. expansum isolates. No substantial differences were observed between isolates of different geographical origins through morphology, patulin accumulation, secondary metabolite profiles and phylogenetic analysis. However, the analysis of polymorphisms revealed 29 haplotypes with a relative separation between isolates of both populations; 13 haplotypes contained Argentinean isolates, while Spanish isolates were separated into 16 haplotypes. The diversity indices of Shannon ( H'= 2.075; H'= 2.402) and Simpson (SiD  = 0.850; SiD  = 0.895) for isolates from Argentina and Spain, respectively, indicated that the diversity of P. expansum is greater in Spain than in Argentina. This distribution could be explained both by the existence of haplotype exchange between both countries, with the ancestral haplotypes originating in Spain, and the subsequent adaptation to the environmental conditions or apples varieties grown in each region. Highlights: Penicillium expansum populations from Argentinean and Spanish apples were compared. P. expansum populations showed low secondary metabolite diversity. Phylogenetic analyses did not allow establishing evolutionary relationships. Relative separation was revealed by analysis of polymorphisms in the β-tub fragment. A significant geographical genetic structure was found in the populations.